Canada before confederation : maps at the exhibition - Duzer, Chet Van; Beck, Lauren (Vernon series in world history., 2018)
Each of the maps featured in this book was showcased in the exhibition "Canada before Confederation: Early Exploration and Mapping," which took place in several locations, both in Canada and abroad, in Fall of 2017. The authors provide a scholarly study highlighting the importance and unique features of each of these jewels of cartographic history, with particular attention paid to how they demonstrate the development of Canadian identity at the same time that they reveal Indigenous knowledge of the lands now known as Canada.